CONDITIONAL DISCONTINUANCE OF CRIMINAL PROCEEDINGS IN POLISH CRIMINAL LAW - Mozgawa-Saj, Marta (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: analysis of the conditions of the use of one of probation measures present in Polish criminal law, namely conditional discontinuance of criminal proceedings. Research methods: legal-dogmatic analysis of the provisions of Criminal Code and the Code of Criminal Procedure, and analysis of avaliable statistics regarding the applicability of conditional discontinuance of criminal proceedings related to total convictions in Poland in the period 1999-2022. Results: the author specifies the prerequisites for conditional discontinuance of criminal proceedings (fault and social harmfulness of the offensive act are minor, the circumstances in which the offensive act was committed do not raise any doubts, the offender having not been previously punished for an intentional offence, positive criminological prospects, the offence being punishable by a custodial sentence not exceeding 5 years), and specifies the period of probation, supervision and obligations of obligations of the offender, as well as the prerequisites for resuming the proceedings (optional and obligatory). Discussion: conditional discontinuance of criminal proceedings is an essential criminal policy tool, and it is the responsibility of judicial authorities to appropriately use this institution as a means for combating relatively minor crime. An analysis of statistical data shows that in recent years, approximately 8 per cent of judgements result in the application of the institution of conditional discontinuance of criminal proceedings (e.g. in 2015 - 8.2 per cent, in 2018 - 9.0 per cent, in 2022 - 8.1 per cent). To sum up, it should be noted that the institution of conditional discontinuance of criminal proceedings is an important tool of criminal policy (as evidenced by the fact that in recent years every 12th adjudication ends with the application of this institution). The current approach to the provision (both in substantive and procedural terms) does not raise any essential doubts.